2021
DOI: 10.17153/oguiibf.636017
|View full text |Cite
|
Sign up to set email alerts
|

Makine Öğrenmesi Teknikleri İle Hisse Senedi Fiyat Tahmini

Abstract: Bu çalışma, Borsa İstanbul Anonim Şirketi (BİST) 30 Endeksi’nde işlem gören firmaların hisse senetlerinin gelecek fiyatlarını tahmin etmeyi amaçlamaktadır. Bu amaçla öncelikle BİST 30 Endeksi firmalarının 2010-2019 yılları arasındaki üçer aylık finansal tabloları temin edilmiş daha sonra bu tablolar vasıtasıyla firmalara ait finansal oranlar hesaplanmıştır. Ayrıca firma hisse senetlerinin aylık kapanış fiyatlarına ulaşılmış ve firmalara ait finansal oranlarla denk olacak şekilde üçer aylık ortalamaları alınmış… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was reported that the prediction accuracy values for the 5-day input were 57.52%, 52.17%, and 63.54% for LSTM, GRU, and BLSTM, respectively. Ustalı et al (2020) aimed to predict the future prices of the stocks of the companies traded in the XU 30 index using Artificial Neural Networks, Random Forest Algorithm, and XGBoost Algorithm. The quarterly average of the monthly closing prices between 31.01.2010 and 31.12.2019 was used as the data set.…”
Section: Literaturementioning
confidence: 99%
“…It was reported that the prediction accuracy values for the 5-day input were 57.52%, 52.17%, and 63.54% for LSTM, GRU, and BLSTM, respectively. Ustalı et al (2020) aimed to predict the future prices of the stocks of the companies traded in the XU 30 index using Artificial Neural Networks, Random Forest Algorithm, and XGBoost Algorithm. The quarterly average of the monthly closing prices between 31.01.2010 and 31.12.2019 was used as the data set.…”
Section: Literaturementioning
confidence: 99%
“…Yani veri seti rassal küçük gruplara ayrılarak karar ağaçları oluşturulur. Tahminleme veya sınıflandırma aşamalarında veri setinden oluşturulan karar ağaçlarının tahminlerinin ortalaması alınır [2].…”
Section: Randomforest(ro)unclassified
“…In recent years, there has been an increase in the number of approaches based on machine learning for popular financial assets such as the Bist100 index, BTC, gram gold, dollar, and brent oil [21][22][23][24][25][26][27][28][29].…”
Section: Experimental Studies For Bist100 Index Btc Gold Dollar and B...mentioning
confidence: 99%